ANALISIS NILAI FEMINISME DALAM FILM TUHAN IZINKAN AKU BERDOSA - Nur Fazri Jafar Awad (Journal of Innovation Research and Knowledge, 2025)
This research is grounded in the persistent dominance of patriarchy in popular media, including films, which often portray women as passive subjects vulnerable to symbolic and physical oppression. The film Tuhan Izinkan Aku Berdosa presents a contrasting narrative by depicting a female protagonist who experiences systemic repression while simultaneously resisting patriarchal structures. This study aims to identify and analyze the feminist values represented in the film through its characters, narrative flow, dialogues, and visual symbols. The research employs a descriptive qualitative method using Roland Barthes’ semiotic framework, examining meanings at the denotative, connotative, and myth levels. The results indicate that the film illustrates multiple forms of gender-based oppression, such as silencing women’s voices, structural violence, sexual exploitation, and patriarchal legitimacy supported by religious and moral narratives. However, the film also highlights women’s resistance through agency, critical awareness, and strategies to expose the hypocrisy of powerful men. The study concludes that the film functions not only as cinematic entertainment but also as an educational medium that articulates radical feminist values. Future researchers are encouraged to examine similar themes in other films or adopt an intersectional feminism approach to explore the diversity of women’s experiences